Comparative Efficacy Of Percussive Massage Gun And Myofascial Release On Lumbar Fascia Trigger Points In Lumbar Myofascial Pain Syndrome – Interventional Study - kumbhar, Shruti; Rayjade, Amrutkuvar (Journal of Neonatal Surgery, 2025)
Background: Lumbar myofascial pain syndrome (LMPS) is a common musculoskeletal disorder characterized by chronic pain, stiffness, and limited mobility in the lower back region. Fascial trigger points play a crucial role in the pathophysiology of LMPS, contributing to pain, inflammation, and muscle dysfunction. Traditional treatment for LMPS often focus on pharmacological interventions, physical therapy, and manual therapies like myofascial release (MFR). Recently, percussive massage gun gained popularity as a novel treatment modality for musculoskeletal pain and inflammation. Methodology: Interventional study conducted on 30 lumbar myofascial pain syndrome patients, participants age ranged from 18-43 years with both genders were included in this study. Myofascial release technique was applied on 15 participants which was group A, and percussive massage gun was applied on 15 participants which was group B, along with conventional treatment in each group. The treatment was given two sessions per week for four weeks, all participants were evaluated pre and post treatment by wagner FPX25 digital algometer was utilized to measure pain pressure threshold, Quebec Back Pain Disability Scale (QBPDC) to measure functional disability of low back pain, Modified Schober’s test was used to calculate the flexion and extension of lumbar spine. Results: This study showed that, Group A significantly lowered disability score than group B, mean value of group A is 22.80 andgroup B is 29.73 (p = 0.0153) andgroup A more effectively reduced in pain pressure threshold than group B, mean value of group A is 1.81 and mean value of group B is 2.28(p = 0.0284). Furthermore, group A also showed great improvement in lumbar ranges than group B, lumbar flexion mean value of group A is 6.10 and mean value of group B is 5.28(p = 0.0009) and lumbar extension mean value of group A is 2.24 and mean value of group Bis 2.00 (p = 0.0169). Conclusion: Myofascial Releaseand Percussive massage gunboth interventions were effective in reducing pain, improving lumbar mobility, and decreasing disability in individuals with Lumbar Myofascial Pain Syndrome. However, Myofascial Release show significantly greater improvement across all outcome measures compared to the percussive massage gun.These findings shows that Myofascial release(MFR) should be considered a more effective therapeutic option for managing lumbar myofascial pain syndrome (LMPS).